Radiomic Features Associated With HPV Status on Pretreatment Computed Tomography in Oropharyngeal Squamous Cell Carcinoma Inform Clinical Prognosis - Song, Bolin; Yang, Kailin; Garneau, Jonathan; Lu, Cheng; Li, Lin; Lee, Jonathan; Stock, Sarah; Braman, Nathaniel M.; Koyuncu, Can Fahrettin; Toro, Paula; Fu, Pingfu; Koyfman, Shlomo A.; et al. (Frontiers in Oncology, 2021)
Purpose: There is a lack of biomarkers for accurately prognosticating outcome in both human papillomavirus-related (HPV+) and tobacco, alcohol related (HPV-) oropharyngeal squamous cell carcinoma (OPSCC). The purpose of this study was to (i) develop and evaluate radiomic signatures on CT scans to predict HPV status, (ii) investigate the prognostic value of the radiomic features for both HPV- and HPV+ patients, (iii) develop and evaluate a clinicopathologic-imaging nomogram involving radiomic, clinical and pathologic factors for disease-free survival (DFS) prediction for HPV+ patients. Experimental design: This retrospective study included 582 OPSCC patients, 462 of which were obtained from The Cancer Imaging Archive (TCIA) with available tumor segmentation, and 120 HPV+ OPSCC patients were from Cleveland Clinic Foundation (CCF, denoted as SCCF). We subdivided the TCIA cohort into training (ST, 180 patients) and validation (SV, 282 patients) based on an approximately 3:5 ratio for HPV status prediction. The top 15 radiomic features that were associated with HPV status were selected using ST and evaluated on SV. Using 3 of these 15 top HPV status-associated features, we created radiomic risk scores for both HPV+ (RRSHPV+) and HPV- patients (RRSHPV-) through a Cox regression model to predict DFS. Nomograms for the HPV+ population (Mp+RRS) were consructed. Both RRSHPV+ and Mp+RRS were used to prognosticate DFS for AJCC 8th edition defined stage I, stage II and stage III patients separately. Results: RRSHPV+ was prognostic for DFS for (i) the whole HPV+ population¬ (Hazard Ratio [HR] = 1.97, 95% confidence interval [CI], 1.35-2.88, p < 0.001), (ii) the AJCC 8th stage I population (HR = 1.99, 95% CI, 1.04-3.83, p = 0.039) and (iii) the AJCC 8th stage II population (HR = 3.61, 95% CI, 1.71-7.62, p < 0.001). HPV+ nomogram Mp+RRS (C-index, 0.59; 95% CI, 0.54-0.65) was also prognostic of DFS (HR = 1.86, 95% CI, 1.27-2.71, p = 0.001) Conclusion: CT-based radiomic signatures are associated with both HPV status and DFS in OPSCC patients. With additional validation, the radiomic signature and its corresponding nomogram could potentially be used for identifying HPV+ OPSCC patients who might be candidates for therapy deintensification.